EVALUASI PROGRAM LAYANAN ONLINE SISTEM INFORMASI REKOMENDASI IZIN SURVEY TANPA ANTRI (SI RISTA) PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN PROBOLINGGO - Agis Aderovi, Mariatul Khiptia; Sucahyo, Imam; Puspitarini, Renny Chandradewi (POPULIKA, 2023)
The large number of researchers who need research permits for various needs such as carrying out their final assignment. When making permits, they still used a manual system, coupled with the complexity during the pandemic, issuing research permits took longer. SI RISTA is an administrative innovation in the field of public services that provides a service in the form of issuing research survey permits. This program was created by the probolinggo district national and political unitary agency, in accordance with Regent Regulation Number 59 of 2021 Concerning the Information System for Recommending Survey Permits Without Queuing (SI RISTA), which explains that this program was created to make it easier for applicants to obtain a survey permit. This evaluation uses the theory put forward by William Dunn. The method of this study uses qualitative methods, in which the results obtained from this study are based on the results of interviews and observations of several relevant informants. The results of research on program evaluation show that this program is in accordance with the needs of research permit applicants in Probolinggo Regency. Keywords: Public Policy, Public Service, Innovation, Bakesbangpol, Evaluation